Analysis of Forms and Usage of Onomatopoeia in Babymetal Band Singer's Song Lyrics - Muhammad Raihan Wicaksono; Haryono (MultiTech Publisher, 2024)
The aim of this descriptive qualitative study discusses the analysis of forms and usage of onomatopoeia in the Babymetal Band singer song lyrics so that listeners can understand the meanings of the lyrics. Using listening and note-taking techniques, data is analyzed by Miles and Huberman's semantic theory. The result concludes that there are 14 contexts in the lyrics containing onomatopoeia that can be categorized into 5 types i.e. Giseigo, Giongo, Gitaigo, Giyougo, Gijougo, and 8 characteristics i.e. Gokon, Oto wo tsumeru, Oto ho haneru, Cho'on, Morpheme “ri”, Hanpukukei, Oto no ichibu koutai, Counter sound Seion and Dakuon. However, the types Gijougo and the characteristic Hanpukukei were most frequently found because Babymetal often uses emotional elements in their music.